Intra-African trade integration - Odjo, Sunday P.; Traoré, Fousseini; Zaki, Chahir (International Food Policy Research Institute, 2019)
Regional integration arrangements have proliferated across Africa over the last 40 years. The most clearly stated objective of this quest for integration is to expand intraregional trade, as it is believed that the harmonization of regulations and policies will help reduce trade costs and facilitate economies of scale. This trend is now being accelerated as African policy makers are pushing for broader integration to realize the long-held desire for pan-African unity in the form of a continental free trade area. This chapter explores how effective regional trade arrangements (RTAs) have been in promoting intraregional trade in Africa. To do this we examine several indicators, since one single indicator cannot capture the multiple dimensions and determinants of trade integration (Bouët, Cosnard, and Laborde 2017).